(untitled) (Muwazah, 2018)
The reality of the lack of women’s role on the political stage has led many to have built important commitments as social reconstruction to increase women’s chances of being more active in the political stage. To realize these objectives various laws and regulations have been created to provide opportunities for women to take an active role in politics. The appearance of women in the political stage in various regions has shown a shift in the political paradigm that wants gender equality where there is a demand for women and men to have equal opportunity in politics.